Optimum supply and utilization of pure oxygen along with nitrogen on the cathode side for thermal stability of a proton exchange membrane fuel cell. (2nd January 2021) - Gadhewal, Ramakant; Thamida, Sunil Kumar; Ananthula, Venu Vinod
ABSTRACT: As the economical operation of Fuel Cells is essential, in this work, a simulation study is carried out on a 3D geometry of the cathode side of a single-layered Proton Exchange Membrane Fuel Cell (PEMFC) since the cathode reaction is the limiting step. The oxygen and nitrogen mass fraction in the inlet feed on the cathode side are varied as well as the total feed flow rate consisting of traces of water vapor. The worst-case scenario of no-cooling that is with an insulated bipolar plate is assumed. This is to test the maximum thermal effect on the membrane. The flow, heat, and mass transfer multiphysics phenomena in the gas diffusion layer and catalyst scaffold layer are simulated using a simplified geometry and an own program in COMSOL Multiphysics software. The electrochemical reaction of oxygen reacting with hydrogen is considered instantaneous reaction at the catalyst surface. A performance factor comprising of power density generated, the maximum temperature and oxygen utilization is defined. It is optimized for the purpose of determining the optimum oxygen mass fraction in feed and net feed flow rate that gives long life thermally and low operating cost of a PEMFC.